066 Impact of long-term teriflunomide treatment on lymphocyte counts and infections in pooled temso and tower studies. Issue 6 (24th May 2018) - Comi, Giancarlo; Macdonell, Richard; Benamor, Myriam; Truffinet, Philippe; Thangavelu, Karthinathan; Mandel, Matt; Freedman, Mark S
Abstract : Introduction: In TEMSO (NCT00134563 ) and TOWER (NCT00751881 ), teriflunomide was associated with early reductions in mean lymphocyte counts, which remained within the normal range. Here, we analyse long-term effects of teriflunomide on lymphocyte counts and infections in pooled TEMSO/TOWER core and extension data (TEMSO extension, NCT00803049 ). Methods: Pooled data from core studies are reported for patients receiving placebo or teriflunomide 14 mg. In the extensions, placebo-treated patients received active treatment; results from pooled core and extension studies are reported for the teriflunomide 14 mg group. Lymphocyte counts were obtained every 2 weeks until Week 24, and every 6 weeks thereafter. Lymphopenia was identified from 2 consecutive lymphocyte counts below LLN and graded by Common Terminology Criteria for Adverse Events. Results: In the core studies, placebo/teriflunomide-treated patients rarely experienced Grade 1 (0.7%/2.1%) or 2 (0.5%/1.4%) lymphopenia. Infections were reported in placebo-treated (40.0%/75.0%) and teriflunomide-treated (73.3%/20.0%) patients with Grade 1 or 2 lymphopenia, respectively. No patients with Grade 1 lymphopenia and 1 placebo-treated patient with Grade 2 lymphopenia developed a serious infection. In the combined core and extension studies, teriflunomide-treated patients (n=1354) experienced few Grade 1 (3.0%) or 2 (2.4%) lymphopenias; infections were reported in 25/40 (62.5%) and 19/33 (57.6%) patients, respectively, vs 718/1281 (56.0%) patients without lymphopenia. Serious infections occurred in patients without lymphopenia (47 patients [3.7%]) and in those with Grade 1 (1 [2.5%]) or Grade 2 (3 [9.1%]) lymphopenia. No Grade 3/4 lymphopenias were recorded. Despite the overall low rate of lymphopenia, occurrence and severity of lymphopenia will also be reported in subgroups of Asian and white patients. Conclusion: In long-term TEMSO and TOWER trials, low-grade lymphopenia was uncommon, with no reports of high-grade lymphopenia. Infection rates were similar in patients with or without lymphopenia, consistent with an immunomodulatory mechanism of action of teriflunomide with limited impact on protective immunity.